2017
DOI: 10.1039/c7ra09006d
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical study on homolytic B–B cleavages of diboron(4) compounds

Abstract: The B–B BDEs of diboron(4) compounds and the Pt–B and Cu–B BDEs of their corresponding complexes were investigated by SOGGA11-X method.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 116 publications
0
12
0
Order By: Relevance
“…This suggests that the recent‐developed V 2 O 5 electrodes have acceptable capacity performance in all three insertion modes. Meanwhile, few results with advanced capacity performance which obviously exceed the theoretical values can be found for all three modes. The unique as‐fabricated porous, hierarchical, or high‐specific‐surface‐area nanostructures as well as the small loaded current are the key points to obtain such exceptional performance.…”
Section: Analysis Of the Electrochemical Performance Of V2o5 And V2o5mentioning
confidence: 99%
“…This suggests that the recent‐developed V 2 O 5 electrodes have acceptable capacity performance in all three insertion modes. Meanwhile, few results with advanced capacity performance which obviously exceed the theoretical values can be found for all three modes. The unique as‐fabricated porous, hierarchical, or high‐specific‐surface‐area nanostructures as well as the small loaded current are the key points to obtain such exceptional performance.…”
Section: Analysis Of the Electrochemical Performance Of V2o5 And V2o5mentioning
confidence: 99%
“…[23][24][25] Among the oxides materials, manganese oxide create a center of attention more due to the merits of natural abundance, low toxicity, structural diversity and multi valance nature. [26][27][28] It has the potential to impact in various fields like catalysis, [10,[29][30][31] supercapacitors, [32,33] and metal-air batteries [5,6] etc. In the recent years, manganese oxides have attracted a great deal of attention towards bifunctional electrocatalyst due to their unique structures and physicochemical properties.…”
Section: Introductionmentioning
confidence: 99%
“…This result is in conformity with the Ppy synthesized by various methods as reported in the literature. [29] In case of nanocomposites, Ag@Ppy-MA, the corresponding amorphous matrix of Ppy was observed with the same broad shape as in the copolymer. It was also observed that the diffraction peaks with high intensities appear at angles corresponding to Ag crystal plains at 37.5°(111), 43.6°(200), 63.8°(220), and 76.8°(311), which may be because of the silver nanoparticles.…”
Section: X-ray Diffractionmentioning
confidence: 79%